Role of Decidual Natural Killer Cells in Human Pregnancy and Related Pregnancy Complications - Zhang, Xiuhong; Wei, Haiming (Frontiers in Immunology, 2021)
Pregnancy is a unique type of immunological process. Healthy pregnancy is associated with a series of inflammatory events: implantation (inflammation), gestation (anti-inflammation), and parturition (inflammation). As the most abundant leukocytes during pregnancy, natural killer (NK) cells are recruited and activated by ovarian hormones and have pivotal roles throughout pregnancy. During the first trimester, NK cells represent up to 50–70% of decidua lymphocytes. Differently from peripheral-blood NK cells, decidual natural killer (dNK) cells are poorly cytolytic, and they release cytokines/chemokines that induce trophoblast invasion, tissue remodeling, embryonic development, and placentation. NK cells can also shift to a cytotoxic identity and carry out immune defense if infected in utero by pathogens. At late gestation, premature activation of NK cells can lead to a breakdown of tolerance of the maternal–fetal interface and, subsequently, can result in preterm birth. This review is focused on the role of dNK cells in normal pregnancy and pathological pregnancy, including preeclampsia, recurrent spontaneous abortion, endometriosis, and recurrent implantation failure. dNK cells could be targets for the treatment of pregnancy complications.